Effect of pecto-intercostal fascial block on extubation time in patients undergoing cardiac surgery: A randomized controlled trial - Wang, Lu; Jiang, Luyang; Xin, Ling; Jiang, Bailin; Chen, Yu; Feng, Yi (Frontiers in Surgery, 2023)
Abstract Objectives: Epidural and paravertebral block reduce the time to extubation in patients undergoing surgery under general anesthesia, but are relatively contraindicated in heparinized patients due to potential risk of hematoma. Pecto-intercostal fascial block (PIFB) is an alternative in such patients. Methods: This is a single-centre randomized controlled trial. Patients scheduled for elective open cardiac surgery were randomized at a 1:1 ratio to receive PIFB (30-ml 0.3% ropivacaine plus 2.5-mg dexamethasone on each side) or saline (30-ml normal saline on each side) after induction of general anesthesia. The primary outcome was time to extubation after surgery. Secondary outcomes included opioid consumption during surgery, postoperative pain scores, adverse events related to opioid and length of stay in hospital. Results: A total of 50 patients (mean age: 61.8 years; 34 men) were randomized (25 in each group). The surgery included coronary artery bypass grafting alone in 38 patients, valve surgery alone in 3 patients, and both in the remaining 9 patients. Cardiopulmonary bypass was used in 20 (40%) patients. The time to extubation was 9.4±4.1 hours in the PIFB group vs 12.1±4.6 hours in the control group (p=0.031). Opioid (sufentanil) consumption during surgery was 153.2±48.3 and 199.4±51.7 μg, respectively (p=0.002). In comparison to the control group, the PIFB group had lower pain score at cough (1.45±1.43 vs 3.00±1.71, p=0.021) and similar pain score at rest at 12 hours after surgery. The two groups did not differ in the rate of adverse events. Conclusions: PIFB decreased time to extubation in patients undergoing cardiac surgery.